Madang ŭl naon amt'ak. The hen who left the yard. - O Sŏng-yun. ([Sŏul] : K'eidi Midiŏ, 2011)
애니메이션영화
Kamdok O Sŏng-yun ;Chejak K'eidi Midiŏ.
DVD, NTSC, region 3.
In Korean
Keywords: Motion picture -- DVD special features; Feature films; Animals -- Juvenile drama